Towards developing an ethical framework for decision making in long-term ventilation in children. Issue 11 (5th June 2018) - Ray, Samiran; Brierley, Joe; Bush, Andy; Fraser, James; Halley, Gillian; Harrop, Emily Jane; Casanueva, Lidia
Abstract : The use of long-term ventilation (LTV) in children is growing in the UK and worldwide. This reflects the improvement in technology to provide LTV, the growing number of indications in which it can be successfully delivered and the acceptability of LTV to families and children. In this article, we discuss the various considerations to be made when deciding to initiate or continue LTV, describe the process that should be followed, as decided by a consensus of experienced physicians, and outline the options available for resolution of conflict around LTV decision making. We recognise the uncertainty and hope provided by novel and evolving therapies for potential disease modification. This raises the question of whether LTV should be offered to allow time for a therapy to be trialled, or whether the therapy is so unlikely to be effective, LTV would simply prolong suffering. We put this consensus view forward as an ethical framework for decision making in children requiring LTV.